Analysis of systemic inflammatory response in the carcinogenic process of uterine cervical neoplasia - Lopes e Lages, Elisa [UNESP]; Belo, Andrezza Vilaca; Andrade, Silvia Passos; Rocha, Monaliza Angela; Freitas, Gustavo Ferreira de [UNESP]; Lamaita, Rivia Mara [UNESP]; Traiman, Paulo [UNESP]; Silva-Filho, Agnaldo Lopes [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
The inflammatory response is an active process in cervical cancer and may act in the progression and/or regression of the lesion. At the site of inflammation, macrophages and neutrophils are present as well as cytokines such as TNF-alpha and IFN-gamma. This study aims to evaluate the inflammatory response levels in women with cervical intraepithelial lesions (CIN) and with squamous cell carcinoma (SCC) of the cervix. Serum samples obtained from women without evidence of disease (n = 30), with CIN (n = 30) and with SCC of the cervix (n = 30) were analyzed for the activities of N-acetylglucosaminidase (NAG) and myeloperoxidase (MPO) by enzymatic assay and the serum levels of TNF-alpha and IFN-gamma by ELISA assay. The activities of NAG and MPO and the level of TNF-alpha were higher in women with CIN compared to the women with SCC. The levels of IFN-gamma were lower in the group of women with CIN compared to the group with SCC. There was not a significant association between the degree of the CIN and the staging of the SCC of the cervix and the degree of inflammation as assessed by the levels of inflammatory markers. The inflammatory response was inversely correlated with the progression of the carcinogenic process. In the three groups, the control group, women with CIN and women with invasive SCC, there was no association between the degree of preinvasive lesions and staging of the SCC of the cervix. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: Cervical cancer; N-acetylglucosaminidase (NAG); Myeloperoxidase (MPO)